Effect of bio-fertilizers on growth and yield of chilli (Capsicum annuum L.) cv Byadagi Dabba at different levels of nitrogen and phosphorus - Niranjan Kumar, B S Sreeramu, K Mahantesh Sajan, K Kempe Gowda, S (Journal of Spices and Aromatic Crops, 2002)
Investigations were carried out to study the effect of nitrogenous and phophatic bio-fertilizers along with different levels of nitrogen and phosphorus on growth and yield of chillies (Capsicum annuum) cv Byadagi Dabba. The maximum plant height, leaf area per plant and dry matter production per plant were in the treatment supplied with 75% N, P plus 100% K in addition to the inoculation of Azotobacter, Azospirillum, phosphate solubilizing bacteria (PSB) and vesicular arbuscular mycorrhiza (VAM). The plants inoculated with Azotobacter, Azospirillum, PSB and VAM along with 75% N, P plus 100% Kproduced more number of fruits per plant and higher yield of dry chillies. Application of bio-fertilizers along with reduced level of chemical fetilizers has beneficial effect compared to application of chemical fertilizers or bio-fertilizers alone.